2021
DOI: 10.1097/aln.0000000000004036
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Transitions in Fibrinolysis after Trauma: Adverse Outcome Is Principally Related to Late Hypofibrinolysis

Abstract: Background The relationship between late clinical outcomes after injury and early dynamic changes between fibrinolytic states is not fully understood. The authors hypothesized that temporal transitions in fibrinolysis states using rotational thromboelastometry (ROTEM) would aid stratification of adverse late clinical outcomes and improve understanding of how tranexamic acid modulates the fibrinolytic response and impacts mortality. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 48 publications
1
30
0
1
Order By: Relevance
“…Gando et al 34 and Wada et al 37 showed that disseminated intravascular coagulation (DIC) with the fibrinolytic phenotype in the acute phase of TBI develops into DIC with the thrombotic phenotype (fibrinolysis shutdown) at a high rate and has a poor prognosis due to organ dysfunction from thrombus deposition. In a secondary analysis of previously collected data from a prospective cohort study, Rossetto et al 38 showed that the development of hypofibrinolytic state (fibrinolysis shutdown) after 24 h with rotational thromboelastometry (ROTEM®; TEM International GmbH, Munich, Germany) was associated with severe TBI patients and increased incidence of multiple organ failure and late mortality. The results of these studies support the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Gando et al 34 and Wada et al 37 showed that disseminated intravascular coagulation (DIC) with the fibrinolytic phenotype in the acute phase of TBI develops into DIC with the thrombotic phenotype (fibrinolysis shutdown) at a high rate and has a poor prognosis due to organ dysfunction from thrombus deposition. In a secondary analysis of previously collected data from a prospective cohort study, Rossetto et al 38 showed that the development of hypofibrinolytic state (fibrinolysis shutdown) after 24 h with rotational thromboelastometry (ROTEM®; TEM International GmbH, Munich, Germany) was associated with severe TBI patients and increased incidence of multiple organ failure and late mortality. The results of these studies support the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these results can be extrapolated to other groups of patients with differential sensitivity to tPA or patients with later onset shutdown warrant further investigation. 48 Second, similar to other studies of trauma, our study included patients with diverse injuries; patients in the hyperfibrinolysis subgroup were generally more severely injured and had greater mortality than shutdown samples. However, inclusion of these patients with clearly distinguished phenotypes increased our ability to identify differences between groups.…”
Section: Discussionmentioning
confidence: 92%
“…85 Changes in fibrinolytic signal in acute trauma victims are dynamic, likely associated with resuscitation and develop over time. 86 Teleologically, abrupt elevation in tissue plasminogen activator after massive injury is followed by a rise in plasminogen-activator inhibitor and potential hypofibrinolysis, which may manifest over the course of resuscitation. 87 The current dilemma of TXA use in acute trauma is the necessity to intervene early (<3 hours) to maximize possible benefit in the highest risk period for hemorrhagic death, balanced with unknown fibrinolytic status until data from viscoelastic or other assays become available.…”
Section: Txa In Traumamentioning
confidence: 99%
“…85 Changes in fibrinolytic signal in acute trauma victims are dynamic, likely associated with resuscitation and develop over time. 86 Teleologically, abrupt elevation in tissue plasminogen activator after massive injury is followed by a rise in plasminogen-activator inhibitor and potential hypofibrinolysis, which may manifest over the course of resuscitation. 87…”
Section: Txa In Traumamentioning
confidence: 99%
See 1 more Smart Citation